Impact of audit committee attributes on esg disclosures: evidence from firms listed in the colombo stock exchange - Edirisinghe, I.C.J.; Abeygunasekera, A.W.J.C. (University of Jaffna, 2022)
Purpose: With the increasing demand for Audit Committees (ACs) to oversee the Corporate Sustainability Reporting (or Environmental, Social, and Governance - ESG disclosures), this study attempted to identify the impact of four AC attributes (AC size, AC members’ financial expertise, AC independence, and meeting frequency of AC) on the CSR practices (using the ESG disclosures as the dependent variable) of listed firms in the Colombo Stock Exchange (CSE). Methodology: Secondary data from 260 CSE listed companies were collected from their 2019/2020 annual reports. Data was analysed using the EViews software, and descriptive statistics were applied together with correlation analysis, and regression analysis to identify the associations between variables. Findings: Analysis indicated a significant positive association between the financial expertise of AC members and the ESG disclosures, while a negative but insignificant relationship between the size of AC and the ESG disclosures. Independence of AC and the meeting frequency of AC indicated a positive but insignificant association with ESG disclosures. The findings clarify the impact of AC attributes on the level of ESG disclosures and organisations can re-organize and influence the AC attributes to facilitate and improve ESG disclosures. Through the lenses of agency and legitimacy theories it was noted that organisations must focus on the AC attributes and provide more voluntary disclosures to reduce the conflict of agency and information asymmetry, because shareholders require more information on sustainability. Research limitations: Apart from the missing data from 22 companies, a reasonable number of annual reports did not have a separate section on ESG reporting practices and the data were extracted perusing the whole annual report. Implications: Managers and policymakers considered sustainability reporting as an acknowledgment on governance and adhere to the required disclosure indicators. Research on improving the ESG disclosure checklist, expanded studies with more AC attributes (such as gender diversity of AC, the independence of the chairs of the AC) togetherwith board characteristics can be focused in the future.
Keywords: Audit committee; Corporate sustainability reporting; ESG disclosures; Voluntary reporting